Simultaneous determination of NG‐monomethyl‐l‐arginine, NG, NG‐dimethyl‐l‐arginine, NG, NG′‐dimethyl‐l‐arginine, and l‐arginine using monolithic silica disk‐packed spin columns and a monolithic silica column. Issue 16 (30th June 2014) - Nonaka, Satoko; Sekine, Masae; Tsunoda, Makoto; Ozeki, Yuji; Fujii, Kumiko; Akiyama, Kazufumi; Shimoda, Kazutaka; Furuchi, Takemitsu; Katane, Masumi; Saitoh, Yasuaki; Homma, Hiroshi
<x xml:space="preserve">Abstract</x> We have developed and validated a high‐performance liquid chromatography method that uses monolithic silica disk‐packed spin columns and a monolithic silica column for the simultaneous determination of NG‐monomethyl‐l‐arginine, NG, NG‐dimethyl‐l‐arginine, and NG, NG′‐dimethyl‐l‐arginine in human plasma. For solid‐phase extraction, our method employs a centrifugal spin column packed with monolithic silica bonded to propyl benzenesulfonic acid as a cation exchanger. After pretreatment, the methylated arginines are converted to fluorescent derivatives with 4‐fluoro‐7‐nitro‐2, 1, 3‐benzoxadiazole, and then the derivatives are separated on a monolithic silica column. l‐Arginine concentration was also determined in diluted samples. Standard calibration curves revealed that the assay was linear in the concentration range 0.2–1.0 μM for methylated arginines and 40–200 μM for l‐arginine. Linear regression of the calibration curve yielded equations with correlation coefficients of 0.999 (r2). The sensitivity was satisfactory, with a limit of detection ranging from 3.75 to 9.0 fmol for all four compounds. The RSDs were 4.3–4.8% (intraday) and 3.0–6.8% (interday). When this method was applied to samples from six healthy donors, the detected concentrations of NG‐monomethyl‐l‐arginine, NG, NG‐dimethyl‐l‐arginine, NG, NG′‐dimethyl‐l‐arginine and l‐arginine were 0.05 ± 0.01, 0.41 ± 0.07, 0.59 ± 0.11, and 83.8 ± 30.43 μM (n = 6), respectively.